Comparative study of nicotine titrations by the colorimetric method of the complex formed with naphthylamine and BrCN, and by the spectrophotometric method in the ultraviolet - Valero, M.; García Villanova, R.; Thomas, J. (Ars Pharmaceutica (Internet), 1965)
1. Alpha-naphthylamine lacks specificity for the colorimetric reaction of nicotine and BrCN. 2. Slight variations in the pH of the medium significantly affect the optimal formation of the colored compound, even with the use of the beta isomer. 3. This influence is even greater in the case of variations in the concentration of BrCN. The optimum concentrations of this are above the solubility limit in the solvents used for the reaction. 4. The colorimetric reaction is valid only for nicotine solutions comprised between 2 and 30, and the error of the determination is higher than the moderately permissible one.